The EFL Rural Students’ Experiences in Coping with Online Learning During the Covid-19 Pandemic - Toni Indrayadi; Aridem Vintoni; Usman Usman (Jurnal Educative: Journal of Educational Studies, 2022)
This study aims to explore the learning experiences of the Indonesian rural students during the Covid-19 pandemic which had transitioned to online learning and solutions. A phenomenological approach was used as a research methodology using semi-structured interviews for the data collection. This study was conducted in one Islamic higher education with seven participants. The data were analyzed through thematic analysis by comparing each participant's interview result in the form of research themes. The five themes that emerged in this study are: adapting to online learning, internet access, learning environment, and learning autonomy. The findings of the study indicate that online learning is a problem for the participants who live in rural areas. These problems were caused by unfamiliarity with the online learning method, unstable internet connection, lack of parents’ support, and learning autonomy. However, all challenges can be solved by students. The findings of the study have implications for government and higher education stakeholders to provide enough facilities for online learning for rural students to participate in the learning process smoothlyPenelitian ini bertujuan untuk mengeksplorasi pengalaman belajar siswa daerah terpencil Indonesia selama Covid-19 yang berfokus pada tantangan dan solusi pembelajaran online dari siswa. Pendekatan fenomenologi digunakan sebagai metodologi penelitian dengan menggunakan wawancara semi terstruktur untuk pengumpulan data. Penelitian ini dilakukan di salah satu Perguruan Tinggi Islam dengan jumlah peserta tujuh orang. Data dianalisis menggunakan analisis tematik dengan membandingkan hasil wawancara masing-masing partisipan dalam bentuk tema penelitian. Lima tema yang muncul dalam penelitian ini adalah adaptasi pembelajaran online, akses internet, lingkungan belajar, dan kemandirian belajar. Temuan penelitian menunjukkan bahwa pembelajaran online merupakan masalah bagi peserta yang tinggal di daerah terpencil. Permasalahan tersebut disebabkan oleh ketidaktahuan terhadap metode pembelajaran online, koneksi internet yang tidak stabil, kurangnya dukungan orang tua, dan kemandirian belajar. Namun, semua tantangan dapat diselesaikan oleh siswa. Temuan penelitian ini berimplikasi kepada pemerintah dan pemangku kepentingan pendidikan tinggi untuk menyediakan fasilitas pembelajaran online yang cukup bagi siswa daerah terpencil untuk berpartisipasi dalam proses pembelajaran dengan lancar.